Critical discourse analysis of all will be fine by Buju Banton: An inspirational song - Hasibuan, Hapni Nurliana H.D; Triyono, Sulis; Sahayu, Wening (LingTera, 2021)
Song lyrics have some purposes, reasons, and messages. It contains various themes such as current and social issues and issues that the songwriter wants to share through the ideology, thoughts and feelings expressions. This research aims at finding out the text analysis, social cognition and social context of the All Will Be Fine song. The research used a qualitative research design. The key instrument of the research is human instrument. In validating the data, this research used the triangulation technique. Further, the data were analyzed using Van Djik's analysis model. It was analyzed through the dimensions of text (macrostructure, superstructure, and microstructure), social cognition and social context. The research used Agih method to analyze three stages of text dimensions and Padan method to determine the social cognition and social context of the song lyric. Based on the analysis that has been done, the results provided that the words of discourse were cohesive, coherent and communicative. In addition, the social cognition diction of the song lyrics has been relatable to the current condition and Covid-19 all around the world as social context.